Improving students' healthy lifestyles based on creative approaches - Bolbekov Elyor Abdimumin o‘g‘li (Zien Journals, 2023)
This article provides information on improving students' healthy lifestyle content based on creative approaches, promoting healthy lifestyles, providing students and adults with certain medical and hygienic knowledge of a healthy lifestyle, and awakening their perceptions of how a healthy lifestyle affects the development of the body.
Keywords: Students; healthy lifestyles; society; medicine